What comes first, negative emotions, positive emotions, or moderate-to-vigorous physical activity?. (March 2019) - Kruk, Magdalena; Zarychta, Karolina; Horodyska, Karolina; Boberska, Monika; Scholz, Urte; Radtke, Theda; Luszczynska, Aleksandra
Abstract: Background: Although there is no doubt that indicators of physical activity (PA), negative and positive emotions are associated, the order in which they operate is not well-established. In this study, we investigated indirect associations between a negative emotions indicator (emotional symptoms of depression; henceforth: depression), a positive emotions indicator (physical activity [PA] liking), and moderate-to-vigorous physical activity (MVPA), in order to identify which one of the three variables is likely to precede the others. Methods: Data were collected twice, with a 7–8-month follow-up. 879 adults from the general population ( N = 879 at Time 1, T1; N = 603 at Time 2, T2) filled in questionnaires measuring depression, PA liking and MVPA. Results: Mediation analyses showed that a higher level of depression (T1) predicted a lower level of PA liking (T2) which in turn explained a lower MVPA level (T2). Additionally, a higher level of PA liking (T1) predicted a lower level of depression (T2), which in turn was associated with a higher MVPA level at T2. Analyses with MVPA operating as the independent variable or the mediator were not significant. Conclusions: Results indicated that both negative and positive emotions precede rather than follow MVPA engagement. Highlights: The interplay between MVPA, positive, and negative emotions was tested. Depression and PA liking were chosen as indicators of emotional responses. 'Depression PA liking MVPA' hypothesis was supported. 'PA liking depression MVPA' hypothesis was also supported. MVPA did not precede subsequent depression or PA liking.